2018
DOI: 10.1097/icl.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Excimer Laser Refractive Surgery Candidates

Abstract: Women with compound myopic astigmatism in the age range of 25 and 35 years are the most frequent users of excimer laser refractive surgery. Less than one-third of laser refractive surgeries are covered by insurance policies. Therefore, proper planning for improving services to this group must be given priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…In our studym there was female predominance. In the study carried out by Kuo, et al 23 in order to identify the characteristics of the patients requesting CRS, the researchers reported that this procedure is mainly sought after by young people and women, in accordance with the investigations of Cumberland, et al 24 in the UK and Hashemi, et al 25 in Iran. This phenomenon can be explained in part by the greater aesthetic desire in women, and may be a reason that explains the prevalence observed in our study.…”
Section: Discussionmentioning
confidence: 69%
“…In our studym there was female predominance. In the study carried out by Kuo, et al 23 in order to identify the characteristics of the patients requesting CRS, the researchers reported that this procedure is mainly sought after by young people and women, in accordance with the investigations of Cumberland, et al 24 in the UK and Hashemi, et al 25 in Iran. This phenomenon can be explained in part by the greater aesthetic desire in women, and may be a reason that explains the prevalence observed in our study.…”
Section: Discussionmentioning
confidence: 69%
“…Hubo predominio de los pacientes de sexo femenino. En el estudio realizado por Kuo, et al 23 con el objetivo de identificar las características de los pacientes que solicitan CRC, los investigadores reportaron que este procedimiento lo buscan sobre todo los jóvenes y las mujeres, en concordancia con las investigaciones de Cumberland, et al 24 en el Reino Unido y de Hashemi, et al 25 en Irán. Este fenómeno puede ser explicado en parte por el mayor deseo estético en las mujeres, y puede ser una razón que explique su predominio en el estudio.…”
Section: Discussionunclassified
“…Based on the latest census, approximately 51% of the Iranian population is in the 20–50 year age group. 15 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%